Double-blind, randomized, placebo-controlled pilot clinical trial with gamma-band transcranial alternating current stimulation for the treatment of schizophrenia refractory auditory hallucinations - Xiaojuan Wang; Xiaochen Zhang; Yuan Chang; Jingmeng Liao; Shuang Liu; Dong Ming (Translational Psychiatry)
Abstract Gamma oscillations are essential for brain communication. The 40 Hz neural oscillation deficits in schizophrenia impair left frontotemporal connectivity and information communication, causing auditory hallucinations. Transcranial alternating current stimulation is thought to enhance connectivity between different brain regions by modulating brain oscillations. In this work, we applied a frontal-temporal-parietal 40 Hz-tACS stimulation strategy for treating auditory hallucinations and further explored the effect of tACS on functional connectivity of brain networks. 32 schizophrenia patients with refractory auditory hallucinations received 20daily 20-min, 40 Hz, 1 mA sessions of active or sham tACS on weekdays for 4 consecutive weeks, followed by a 2-week follow-up period without stimulation. Auditory hallucination symptom scores and 64-channel electroencephalograms were measured at baseline, week2, week4 and follow-up. For clinical symptom score, we observed a significant interaction between group and time for auditory hallucinations symptoms (F(3,90) = 26.964, p < 0.001), and subsequent analysis showed that the 40Hz-tACS group had a higher symptom reduction rate than the sham group at week4 (p = 0.036) and follow-up (p = 0.047). Multiple comparisons of corrected EEG results showed that the 40Hz-tACS group had higher functional connectivity in the right frontal to parietal (F (1,30) = 7.24, p = 0.012) and right frontal to occipital (F (1,30) = 7.98, p = 0.008) than the sham group at week4. Further, functional brain network controllability outcomes showed that the 40Hz-tACS group had increased average controllability (F (1,30) = 6.26, p = 0.018) and decreased modality controllability (F (1,30) = 6.50, p = 0.016) in the right frontal lobe compared to the sham group. Our polit study indicates that 40Hz-tACS combined with medicine may be an effective treatment for targeting symptoms specific to auditory hallucinations and altering functional connectivity and controllability at the network level.